1997
DOI: 10.1046/j.1365-2036.1997.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐perceived severity of irritable bowel syndrome in relation to symptoms, health resource utilization and quality of life

Abstract: Aim: In this study of patients with irritable bowel syndrome (IBS), we evaluated the relationship between patient‐rated severity of IBS and patients' physical and psychological symptoms, health care resource use and quality of life. Methods: One hundred and twenty‐six patients diagnosed with IBS were administered a series of questionnaires, including the Bowel Symptom Checklist, the Symptom Checklist‐90 R (a psychological symptom checklist), the IBSQOL (a disease‐specific quality of life instrument), the SF‐36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
1
11

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(113 citation statements)
references
References 22 publications
4
97
1
11
Order By: Relevance
“…Health-related QoL is affected significantly in patients with IBS compared to the general population. The health-related QoL is associated with perceived IBS severity defined by the overall disease limitations rather than symptoms and appears to improve in treatment responders and correlates with symptom improvement [30,31] . For that reason, the SF-36 model, a general health status instrument, was used in our study to assess QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Health-related QoL is affected significantly in patients with IBS compared to the general population. The health-related QoL is associated with perceived IBS severity defined by the overall disease limitations rather than symptoms and appears to improve in treatment responders and correlates with symptom improvement [30,31] . For that reason, the SF-36 model, a general health status instrument, was used in our study to assess QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Using an IBS-specific QoL instrument (IBSQoL), Hahn and colleagues found that patients with severe IBS had significantly poorer scores in physical functioning, social functioning, energy/fatigue, mental health, and role limitations due to emotional and physical components than those with moderately severe disease [Hahn et al 1997]. A recent international Internet survey of 1966 IBS patients [Drossman et al 2009] confirmed these earlier findings, showing that patients with severe IBS scored lower than those with less severe disease in all domains of the IBSQoL and had more days of restricted usual/social activities.…”
Section: Impact Of Irritable Bowel Syndromementioning
confidence: 99%
“…Alosetron has been shown to significantly improve IBS-related abdominal pain and discomfort in randomized, double-blind clinical trials (Figure 3) [Krause et al 2007;Camilleri et al 2001Camilleri et al , 2000. [Hahn et al 1997]. Using the same instrument, Gralnek and colleagues compared HRQoL scores from patients with IBS with scores collected previously from patients with moderate to severe gastroesophageal reflux disease (GERD), diabetes mellitus (DM), dialysis-dependent end-stage renal disease (ESRD), and depression [Gralnek et al 2000].…”
Section: Efficacy Of Alosetronmentioning
confidence: 99%
“…43 One study has used an IBS-speci®c quality of life questionnaire and a general quality of life questionnaire (the SF-36) to examine the association between selfperceived severity and quality of life in patients attending a tertiary care facility. 44 The disease-speci®c questionnaire showed that patients with mild and moderate IBS were not signi®cantly different but those with severe or very severe IBS rated their quality of life signi®cantly lower for physical functioning, role physical, role emotional, social functioning, energy and mental health, compared with those with moderate IBS. As might be expected, the SF-36 results revealed that the poorest health for all dimensions was reported by patients with very severe IBS but the other groups also showed signi®cant impairment of their quality of life.…”
Section: Quality Of Lifementioning
confidence: 99%